Tofacitinib is associated with attainment of the minimally important reduction in axial magnetic resonance imaging inflammation in ankylosing spondylitis patients. (26th April 2018) - Maksymowych, Walter P; Heijde, Désirée van der; Baraliakos, Xenofon; Deodhar, Atul; Sherlock, Sarah P; Li, David; Fleishaker, Dona; Hendrikx, Thijs; Kanik, Keith S
Abstract: Objectives: Minimally important changes (MICs) for SPondyloArthritis Research Consortium of Canada (SPARCC) MRI scores are ⩾2.5 for SI joint and ⩾5 for spine. This post hoc analysis assessed achievement of MIC in SPARCC scores in biologic-naïve patients with AS treated with tofacitinib or placebo, and correlation with clinical responses. Methods: Adult AS patients in a 12-week phase 2 study ( n = 207) were randomized 1: 1: 1: 1 to tofacitinib 2, 5 or 10 mg twice daily (BID) or placebo. MIC in SPARCC SI joint and spine scores were assessed for patients with available MRI data ( N = 164; 79%). Clinical endpoints at week 12, including Assessment of SpondyloArthritis international Society 20% improvement (ASAS20), were compared between patients achieving/not achieving MIC. Results: A greater proportion of patients achieved MIC with tofacitinib 2, 5 and 10 mg BID vs placebo for SI joint (28.6, 38.6, 29.6 vs 11.8%) and spine scores (29.3, 36.4, 40.9 vs 11.8%). Generally, a greater proportion of patients treated with tofacitinib 2, 5 and 10 mg BID or placebo, respectively, who achieved MIC for SI joint and spine scores achieved ASAS20 (SI joint: 75.0, 88.2, 69.2, 75.0%; spine: 91.7, 85.7, 72.2, 75.0%) vs patients who did not achieve MIC (SI joint: 51.7, 84.0, 58.1, 48.3%; spine: 46.4, 85.7, 53.8, 48.3%). Numerically greater responses were seen in those patients achieving vs not achieving MIC across a range of other efficacy assessments. Conclusion: Approximately one-third of tofacitinib-treated AS patients experienced clinically meaningful reductions in spinal MRI inflammation at week 12. Patients achieving MIC for MRI inflammation had greater clinical response.